1989
DOI: 10.1042/cs0770043
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Proteinuria and Reduction in Number of Anionic Sites on the Glomerular Basement Membrane in Rabbits by Infusion of Human Nephrotic Plasma in Vivo

Abstract: 1. Intraortic suprarenal infusion in vivo of New Zealand White rabbits with plasma from patients with the nephrotic syndrome reduced the number of anionic sites labelled by the cationic polymer polyethyleneimine in the lamina rara iterna to 14.0 +/- 2.7 per 1000 nm of lamina rara interna (mean +/- SD) compared with 18.7 +/- 2.1 (P less than 0.005) after infusion of plasma from normal subjects. 2. Proteinuria increased in all nine animals infused with nephrotic plasma and in two of seven infused with control pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The contribution of agrin may be crucial regarding its homogeneous presence in the GBM ( Figure 3) and its abundance in isolated glomeruli (Table 2). Hence, agrin could be essential to maintain charge selectivity during ultrafiltration (Kanwar et al 1991;Vernier et al 1992;Wilkinson et al 1989). …”
Section: Discussionmentioning
confidence: 99%
“…The contribution of agrin may be crucial regarding its homogeneous presence in the GBM ( Figure 3) and its abundance in isolated glomeruli (Table 2). Hence, agrin could be essential to maintain charge selectivity during ultrafiltration (Kanwar et al 1991;Vernier et al 1992;Wilkinson et al 1989). …”
Section: Discussionmentioning
confidence: 99%
“…In rats, serum factors [14,15] and supernatants from IMLNS PBMC cultures [16,17], when injected into the renal artery, have been shown to induce albuminuria [14,16,17] and to decrease the GBM anionic sites [15][16][17]. We reported that serum interleukin-8 (IL-8) levels are increased in IMLNS patients in relapse.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have demonstrated increased urinary protein excretion after infusion into the rat circulation of plasma or serum from patients with IMLNS as well as supernatant from IMLNS PBMC cultures [9,10,11,12,13,14]. Previous studies reported injecting the tested substance into the rat circulation in vivo using a comparatively large fluid volume within a short period of time (usually less than 1 h).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data showing the induction of proteinuria in rats upon the injection of supernatants from PBMC cultures from IMLNS patients in relapse, plasma or serum of the same patients, or a factor produced by human T cell hybridoma have supported the hypothesis of a circulating factor causing proteinuria in IMLNS [9,10,11,12,13,14,15]. We have conducted experiments showing that a cytokine secreted by PBMC from patients with IMLNS in relapse induced proteinuria in rats after 5 days of continuous intrarenal arterial infusion [9].…”
Section: Introductionmentioning
confidence: 99%